Perception of Learning Skills, Confidence, Application of Knowledge and Satisfaction of Nursing Students Towards Online Practice in Mental Health Nursing and Psychiatry Practicum - Chiangkuntod , Suwanna; Angsukiattitavorn, Suleemas; Jirakunjana , Thantip; Suntudhan , Sirina (Journal of Nursing, Siam University, 2023)
This descriptive research aimed to study satisfaction. 21st-century learning skills and confidence in caring for psychiatric patients from online practice in mental health nursing and psychiatry. The population consisted of 134 nursing students in the third year of the Academic Year 2020 who were registered in the Mental Health and Psychiatric Nursing Practice Course. All students were practice by using Blended Learning. Emphasis is placed on role-play for case studies by teachers in each group and face-to-face. The four activities' requirements for each student were 1) group therapy activities 2) therapeutic communication 3) case studies and 4) case study for group conference. The instruments consisted of demographic data, a satisfaction questionnaire, self-assessment of the 21st century learning skills, self-confidence to caring psychiatric patient and the practical knowledge test. Data were analyzed by descriptive statistics, mean, percentage, and inferential statistics comparing differences in confidence scores and practical knowledge application scores by paired-t test. The results showed that 112 students (83.6%) were willing to respond to the questionnaire. The most satisfaction was the usually opportunity to discuss (74.1%) while the lowest of satisfaction was the limited time for case studies conference (9.8%). The most enhancement of 21st-century learning skills is communication skills (36.6%). Comparing between before and finished practice courses the research found that self-confidence in caring for psychiatric patients and applied knowledge to practice scores were also improved with statistical significance at the .05 level.